2018
DOI: 10.4236/psych.2018.92015
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Mindfulness Improves Decision Making and Future Prospects

Abstract: With the popularity of mindfulness training among different groups of people, more and more attention has been paid to the positive role of mindfulness. In particular, the improvement of mindfulness on decision-making has been respected by the elite management and practitioners in different industries. There are also different forms of experimental paradigms for different types of decision-making behaviors in research methods. Both behavioral evidence and imaging evidence show that mindfulness training can imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Cognitive biases are responsible for many of the behaviors that deviate from what would be considered rational in a given situation. Research has shown evidence supporting the idea that mindfulness meditation could reduce the effect of some well-known cognitive biases ([ 1 , 2 , 3 , 4 ]; for examples).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cognitive biases are responsible for many of the behaviors that deviate from what would be considered rational in a given situation. Research has shown evidence supporting the idea that mindfulness meditation could reduce the effect of some well-known cognitive biases ([ 1 , 2 , 3 , 4 ]; for examples).…”
Section: Introductionmentioning
confidence: 97%
“…Trait mindfulness can also decrease the influence of some cognitive biases related to decision-making [ 1 , 2 , 3 , 4 , 32 ] by placing meditators in an analytical position to observe their environment and their own bodily and mental events [ 3 ]. It can also improve working memory capacity by decreasing mind-wandering [ 33 ], keeping one’s attention focused on the present moment [ 1 ], improving one’s ability to explore one’s own values and priorities [ 3 ] and by improving the ability to regulate emotional states recognized to be influencing decision-making [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, research has shown that mindfulness changes the brain in ways that could affect leaders. Leaders practicing mindfulness have demonstrated less emotional reactivity and greater awareness of stress, 15 have exhibited more self-control, 52 have higher assessed leadership by subordinates, 53 have shown greater flexibility, 54 demonstrated improved decision making, 55 and better managed the work environment. 56 In higher tempo occupations (military and nursing), mindfulness training improved attention and arousal regulation, 57 decreased mental workload and cortisol response, 58 and acted as a stress buffer.…”
Section: Introductionmentioning
confidence: 99%